Halogen bond-modulated solid-state reordering and symmetry breaking of azahelicenes - Juncong Liang; Fuwei Gan; Guoli Zhang; Chengshuo Shen; Huibin Qiu (Nature Communications)
Abstract Spontaneous symmetry breaking predominately occurs during the aggregation of discrete molecules in solution. Herein, we report a unique solid-state symmetry breaking process of dynamically chiral aza[4]helicenes that emerged in vacuum-driven transformation of halogen bond-woven crystals. Due to the weak feature of the halogen bonding, the halides in the cocrystals can be completely removed under vacuum at an elevated temperature. Interestingly, the aza[4]helicene molecules released from the halogen bond network solely adopt one chiral conformation upon reordering and symmetry breaking instantly occurs in a solid state. The Cotton effects gradually increase with the extension of vacuum–heating treatment, indicating a unidirectional transformation of the chiral conformations and an amplification of symmetry breaking during the solid-state reorganization. Moreover, the use of aza[6]helicene as a chiral inducer further enables a precise manipulation for the absolute configuration of the solid-state symmetry breaking, paving a distinctive route to chiral organic materials from achiral/racemic precursors.